As antinomias do ensino de filosofia: caminhos e possibilidades para o seu ensino à luz da literatura - Costa, José Luiz (2021)
This dissertation presents an analysis of the teaching of philosophy in Brazil, which seeks to identify the course of teaching this discipline under the legislation that regulates Brazilian education and the ways in which public policies address this issue, which is addressed in all legislation with entirely skewed ideological orientations. The teaching of philosophy itself is also the subject of this work, which addresses some contributions on the teaching of philosophy, reading different authors who have dealt with this theme, showing that thinking about the teaching of philosophy is already an eminently philosophical task, which leads us to a long but fruitful debate, demonstrating possibilities of various forms of teaching the subject in focus. The objective of this work is to demonstrate that one of the possibilities of teaching philosophy is in the relationship it establishes with literature and vice versa. Therefore, we sought to bring the student closer to philosophy through reading literary texts within the youth category, which in theory presents itself as a more pleasurable type of reading. What could be seen in practice is that students become more interested in philosophy when they realize that it is dealing with issues that are so close to them.